Korean Ceramics : the Beauty of Natural Forms. - Koehler, Robert (Korea essentials., 2013)
The most well-known Korean ceramics are the celadon of the Goryeo Dynasty (918-1392) and the white porcelain of the ensuing Joseon Dynasty (1392-1910). ... The celadons of Goryeo, their grace and color tinged with feminine beauty, symbolized an aristocratic Buddhist culture, while the white porcelains from the Joseon period are thought to typify the bureaucratic and scholarly Confucian society and were essentially masculine in tone, vigorous and orderly. ... Korea's traditional ceramic wares serve as a barometer for understanding Korean culture in that they most accurately reflect Korean a.